2021
DOI: 10.1155/2021/6696636
|View full text |Cite
|
Sign up to set email alerts
|

MiR-6869-5p Induces M2 Polarization by Regulating PTPRO in Gestational Diabetes Mellitus

Abstract: The role of microRNA (miRNA) in gestational diabetes mellitus has been widely investigated during the last decade. However, the altering effect of miR-6869-5p on immunity and placental microenvironment in gestational diabetes mellitus is largely unknown. In our study, the expression of miR-6869-5p was documented to be significantly decreased in placenta-derived mononuclear macrophages, which was also negatively related to PTPRO. Besides, PTPRO was negatively regulated by miR-6869-5p in placenta-derived mononuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Stirm et al (60) reported conflicting results on the expression of let-7g. These authors reported higher expression of let-7g in the screening group, however, no difference was observed in the validation group in whole blood samples of German women with GDM compared to controls in the screening group (60) Other articles included in this review reported differential miRNA expression, yet these miRNAs were identified in single studies only (36,37,43,44,48,50,57,59,69,71,74,76,77,80,81).…”
Section: Qualitative Synthesis Of Studiesmentioning
confidence: 87%
See 1 more Smart Citation
“…Stirm et al (60) reported conflicting results on the expression of let-7g. These authors reported higher expression of let-7g in the screening group, however, no difference was observed in the validation group in whole blood samples of German women with GDM compared to controls in the screening group (60) Other articles included in this review reported differential miRNA expression, yet these miRNAs were identified in single studies only (36,37,43,44,48,50,57,59,69,71,74,76,77,80,81).…”
Section: Qualitative Synthesis Of Studiesmentioning
confidence: 87%
“…Other articles included in this review reported differential miRNA expression, yet these miRNAs were identified in single studies only ( 36 , 37 , 43 , 44 , 48 , 50 , 57 , 59 , 69 , 71 , 74 , 76 , 77 , 80 , 81 ).…”
Section: Qualitative Synthesis Of Studiesmentioning
confidence: 99%
“…It is reported that PTPRO plays an important role in tumorigenesis by regulating cell proliferation, migration, invasion and inflammation [ 7 ]. Besides, PTPRO has been proved to be highly expressed in placenta-derived macrophages from patients with gestational diabetes mellitus and could participate in maintaining placental microenvironment balance [ 19 ]. Furthermore, literature has demonstrated that PTPRO expression is upregulated in placental mononuclear cells of patients with PE [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-6869-5p was considerably downregulated in placenta-derived macrophages from GDM patients. It prevents macrophage from targeting PTPRO and promotes macrophage polarization to M2-type cells, thus preventing macrophage proliferation and inflammation, and maintaining the balance of the placental microenvironment [ 76 ]. In addition, one study identified 22 dysregulated exosomal miRNAs in the plasma of pregnant women with GDM and verified that upregulated miR-423-5p and downregulated miR-122-5p, miR-148a-3p, miR-192-5p and miR-99a-5p could be used as early predictors of GDM.…”
Section: Role Of Ncrnas In Gdmmentioning
confidence: 99%